Zika Virus Infection Modulates Extracellular Vesicle Biogenesis and Morphology in Human Umbilical Cord Endothelial Cells: A Proteomic and Microscopic Analysis - Manuel Adrián Velázquez-Cervantes; Arturo Flores-Pliego; Yazmín Rocío Benitez-Zeferino; Victor Javier Cruz-Holguín; Luis Herrera Moro-Huitron; Addy Cecilia Helguera-Repetto; David Eduardo Meza-Sánchez; José Luis Maravillas-Montero; Nicolás Cayetano-Castro; Javier Mancilla-Ramírez; Aurora Casarrubias-Betancourt; Guadalupe León-Reyes; et al. (Microorganisms, 2025)
Infection with Zika virus (ZIKV) is a perinatal health problem and a vertical infection that promotes neurological fetal damage. ZIKV infects different cellular components at the maternal–fetal interface, including umbilical cord endothelial cells (HUVECs). Extracellular vesicles (EVs) are cellular components that mediate extracellular communication. Viruses have the capacity to hijack and modify the biogenesis machinery of EVs for their own benefit. The present work provides proteomic results (2D electrophoresis) that show the regulation of the expression of proteins involved in autophagy, oxidative stress, and exosome biogenesis in HUVECs infected with ZIKV. We confirmed that Alix and CD9 proteins were downregulated following the infection. Additionally, EVs isolated from infected cells showed the expression of Alix, and CD9 was increased in contrast to the mock condition. Interestingly, nanoparticle tracking and cryo-microscopy assays revealed that these EVs showed an increase in the quantity and size of ZIKV infection to differences in mock conditions. Furthermore, EVs isolated from infected cells showed infectivity, and both RNA and viral proteins were detected. Finally, our cryo-microscopy analysis revealed that the viral infection promoted morphological changes in these extracellular vesicles to identify vesicles with double and triple vesicles and electrodense and double membranes. In conclusion, our data suggest that ZIKV infection can modulate cellular factors involved in the formation and morphology of EVs in HUVECs. Furthermore, these EVs carry viral elements that may contribute to the dissemination of infection. Future studies aimed at the proteomic and lipidomic composition analyses of these EVs are needed to understand the biological implications in vertical infection.